Bank connections and small business performance: Evidence from Canadian survey data. (18th August 2020) - Gill, Amarjit; Wilson, Craig
Abstract: We investigate how, as a form of social capital, connections between small business owners and their bankers affect the performance of small businesses in Canada through influencing capital structure efficiency. Owners of private Canadian small businesses were asked about their perceptions regarding bank connections, capital structure efficiency, and the performance of their small businesses. Using principal component analysis, we find that bank connections help small business owners improve capital structure efficiency. Connections are also associated with lower interest rates; however, we find that they improve performance primarily through their improvement of capital structure efficiency rather than reduced interest rates. These findings may prove practically useful for business owners, bankers, and other stakeholders by illustrating how effective policies that help link small business owners with bankers can improve firm performance through access to capital and professional advice.